(untitled) (Práxis Educativa, 2025)
One of the contemporary challenges in education is to design curricula and training programs for teacher education that are capable of providing future teachers with experiences that combine theory and practice to promote professional development. Thus, this article aims to analyze the impact of teaching immersion in the Pedagogical Residency Program (PRP) on the training of Chemistry teachers. The research has a qualitative approach with a descriptive purpose, focusing on two PRP Chemistry Centers from two Higher Education Institutions. Documentary analysis, interviews, and questionnaires were conducted, and the data were analyzed using Content Analysis. The study highlights that the PRP can integrate multiple types of knowledge, social actors, and fields of action to foster and build a collective and dialogical identity among the different actors who shape their spaces and processes through teaching immersion. Keywords: Teacher training. Professionalism. Teaching immersion.